Nilai-Nilai Ekonomi Islam dalam Berwirausaha - Ahmad Muhtar Syarofi (IQTISHODUNA: Jurnal Ekonomi Islam, 2016)
In the past decade emerged a new innovation in the economic system that the world is consuming enough economic system of Islam or sharia economy. The presence of this economic system brings a new color in the global economic system that is a century dominated economic system kapitalis.Sistem berasas Islamic economic justice and humanity into alternative which began ogled even in western countries heart of the emergence of capitalism. By looking at the realities honestly and objectively, then people realize that mental foster entrepreneurship is a significant breakthrough and can not be delayed any longer. We all have to think to look and move in that direction. In Islam, both in concept and practice, entrepreneurial activity is not a stranger, it is often practiced by the Prophet, his wife, friends, and also the scholars in the land air.Islam not just talk about entrepreneurship (although the term self-employment and hard work), but immediately put it into practice in the life nyata.Lembaga education through its practitioners should be more concrete in preparing kegiatanpembelajaran program that can actually encourage the growth and development of entrepreneurial spirit mulaid ari elementary school to college.